Anti-interleukin-6 Antibody Clazakizumab in Antibody-mediated Renal Allograft Rejection: Accumulation of Antibody-neutralized Interleukin-6 Without Signs of Proinflammatory Rebound Phenomena. Issue 2 (26th January 2023) - Borski, Anita; Eskandary, Farsad; Haindl, Susanne; Doberer, Konstantin; Mühlbacher, Jakob; Mayer, Katharina A.; Budde, Klemens; Halloran, Philip F.; Chong, Edward; Jilma, Bernd; Böhmig, Georg A.; Wahrmann, Markus
Abstract : Background: Blockade of interleukin-6 (IL-6) has emerged as a promising therapeutic option for antibody-mediated rejection. Subtherapeutic anti-IL-6 antibody level or treatment cessation following prolonged cytokine neutralization may result in proinflammatory rebound phenomena via accumulation of IL-6 and/or modulated gene expression of major components of the IL-6/IL-6 receptor (IL-6R) axis. Methods: We evaluated biologic material obtained from a randomized controlled, double-blind phase 2 trial designed to evaluate the safety and efficacy of the anti-IL-6 monoclonal antibody clazakizumab in late antibody-mediated rejection. Twenty kidney transplant recipients, allocated to clazakizumab or placebo, received 4-weekly doses over 12 wks, followed by a 40-wk extension where all recipients received clazakizumab. Serum proteins were detected using bead-based immunoassays and RNA transcripts using quantitative real-time polymerase chain reaction (peripheral blood) or microarray analysis (serial allograft biopsies). Results: Clazakizumab treatment resulted in a substantial increase in median total (bound and unbound to drug) serum IL-6 level (1.4, 8015, and 13 600 pg/mL at 0, 12, and 52 wks), but median level of free (unbound to drug) IL-6 did not increase (3.0, 2.3, and 2.3 pg/mL, respectively). Neutralization of IL-6 did not boost soluble IL-6R or leukocyte or allograft expression of IL-6, IL-6R, and glycoprotein 130 mRNA. Cessation of treatment at the end of the trial did not result in a meaningful increase in C-reactive protein or accelerated progression of graft dysfunction during 12 mo of follow-up. Conclusion: Our results argue against clinically relevant rebound phenomena and modulation of major components of the IL-6/IL-6R axis following prolonged IL-6 neutralization with clazakizumab.